Design of a Seaweed Draining and Drying Machine Using Hybrid Energy - Agri Suwandi; Alif Fachrudin; Djoko Setyanto (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
Seaweed is a plant that is adaptable and is used in a variety of industries, such as food, cosmetics, and medication. However, the current seaweed processing technique, which entails sun drying, is still highly traditional and requires a significant amount of time. To speed up draining and drying seaweed, we developed a hybrid energy-powered seaweed draining and drying. The tool capacity of this design is 50 kg, and it applies the Pahl and Beitz method. The selected design is variant 3 with the highest weight value of 7.74. The design outcomes produce the following tool specifications the drive is equipped with a diesel motor with a power of 3.5 Hp, 2.6 kW, and 3600 rpm, as well as three solar panels of the MCS1100 model, each with a capacity of 100 Wp. The container dimensions of 382 mm diameter and 500 mm height. The seaweed is to be dried at a rate of 29,3 kg/m2 per hour. The galvanized steel frame yielded a maximum working stress value of 126.223 N/mm2, which is lower than the material's yield strength value of 203.943 N/mm2. On the shaft made of S45C8 steel, the maximum working stress value after applying the load is 66.83 N/mm2, which is also less than the material's yield strength value of 350 N/mm2. This indicates that the stand and shaft design is safe, as the simulation process's maximum stress value does not surpass the material's yield strength value.